2017
DOI: 10.1021/acs.jpclett.7b02052
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Photodesorption of CO from Charged Point Defects on TiO2(110)

Abstract: The adsorption and photochemistry of CO on rutile TiO(110) are studied with scanning tunneling microscopy (STM), temperature-programmed desorption, and angle-resolved photon-stimulated desorption (PSD) at low temperatures. Site occupancies, when weighted by the concentration of each kind of adsorption site on the reduced surface, show that the adsorption probability is the highest for the bridging oxygen vacancies (V). The probability distribution for the different adsorption sites corresponds to very small di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…3(a)], the stability of the CO adsorption at nonpolaronic Ti 5c sites (i.e. CO+S1 configurations, down pointing triangles) increases with an increasing distance (a,b)] originate from a smaller number of available adsorption sites, as compared to the non-polaronic Ti 5c sites [39].…”
Section: (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…3(a)], the stability of the CO adsorption at nonpolaronic Ti 5c sites (i.e. CO+S1 configurations, down pointing triangles) increases with an increasing distance (a,b)] originate from a smaller number of available adsorption sites, as compared to the non-polaronic Ti 5c sites [39].…”
Section: (A)mentioning
confidence: 99%
“…CO adsorption on the rutile (110) surface is a well-studied phenomenon from both theoretical and experimental points of view [37][38][39][40][41][42][43], yet controversies appear even in elementary issues. Beyond a general consensus on the local geometric properties (CO molecules adsorb vertically at Ti 5c sites at low coverage) [37,38], conflicting outcomes have been reported, which either suggest [39] or exclude [40][41][42] the possibility of CO adsorption at V O sites, in the latter case endorsing a major role played by the fivefold-coordinated Ti 5c sites at S0. We show that the apparent disagreements in the literature can be resolved by a proper treatment of polarons and their interaction with adsorbates, by combining density functional theory (DFT) simulations [44,45] with scanning tunneling microscopy (STM) and atomic force microscopy (AFM).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we use the rutile TiO 2 (110) surface containing an O V and a CO molecule as a classic photocatalytic system to probe the interaction of EPs and adsorbates. Although experiments have demonstrated that defective rutile TiO 2 (110) with adsorbed CO exhibits good photocatalytic activity, 32 , 34 , 35 the dynamics of coupled CO and EPs have not been fully established. Such analysis is challenging for the following reasons.…”
Section: Introductionmentioning
confidence: 99%
“…22 Recent scanning tunneling microscopy (STM) studies have demonstrated that CO molecules adsorb preferentially at or near particular defect sites (V O or OH b ) on reduced or hydroxylated rutile TiO 2 (110) surfaces (r-TiO 2 (110) or h-TiO 2 (110), respectively). 26,27 However, the differences in the CO binding energies between the various adsorption sites are quite small (<0.02 eV). 27 UV irradiation leads to CO desorption from TiO 2 (110).…”
Section: Introductionmentioning
confidence: 99%